2020
DOI: 10.1021/acs.orglett.0c02986
|View full text |Cite
|
Sign up to set email alerts
|

Rh-Catalyzed Annulation of Benzoic Acids, Formaldehyde, and Malonates via ortho-Hydroarylation to Indanones

Abstract: A three-component reaction from readily available low-cost materials of benzoic acids, formaldehyde, and malonates for the preparation of indanones by rhodium catalysis is reported. The annulation is initiated by an ortho-hydroarylation of benzoic acids, and a Lewis acid is not required. The solvent has a significant influence to the reaction, and 2-substituted or nonsubstituted indanones are obtained by the change of solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 74 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…The indanone scaffold can be accessed by carbocyclization, hydroacylation, [4+1] cycloaddition, and carboxylic acid directed annulation under Rh catalysis. [28][29][30] In 2020, the Sharma group proposed a new synthesis method of the 3-trifluoromethyl indanone scaffold. Rh(III) catalyzed the reaction of N-methoxybenzamide with b-trifluoromethyl-a,b-unsaturated ketone to synthesize the 3-trifluoromethyl indanone product with the involvement of trifluoroethanol.…”
Section: Introductionmentioning
confidence: 99%
“…The indanone scaffold can be accessed by carbocyclization, hydroacylation, [4+1] cycloaddition, and carboxylic acid directed annulation under Rh catalysis. [28][29][30] In 2020, the Sharma group proposed a new synthesis method of the 3-trifluoromethyl indanone scaffold. Rh(III) catalyzed the reaction of N-methoxybenzamide with b-trifluoromethyl-a,b-unsaturated ketone to synthesize the 3-trifluoromethyl indanone product with the involvement of trifluoroethanol.…”
Section: Introductionmentioning
confidence: 99%
“…We had recently shown that a three-component annulation of benzoic acids and formaldehyde as well as malonates gave indanones via aromatic C–H activation by rhodium catalysis . We questioned if a proposed key intermediate II could be formed through the rhodium activation of the vinylic C–H bond of acrylic acids (Scheme ).…”
mentioning
confidence: 99%
“…16 The strategy of combining positionally selective C− H activation and multicomponent reaction would lead to We had recently shown that a three-component annulation of benzoic acids and formaldehyde as well as malonates gave indanones via aromatic C−H activation by rhodium catalysis. 17 We questioned if a proposed key intermediate II could be formed through the rhodium activation of the vinylic C−H bond of acrylic acids (Scheme 2). This was then thought to undergo an insertion into methylenemalonates, which could be formed in situ by formaldehyde and malonates under the reaction conditions, to generate intermediate IV.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, in the early exploration, such transformation could not be realized by using any kind of copper catalyst, so we turned to think about introducing a second catalytic system to develop a bimetallic system. In the latest years, various works involving transition-metal-catalyzed C–H activation to fulfill the intermolecular annulation were reported . Among this literature, benzoic acid and benzamide derivatives were highlighted as the most common substrates to react with different alkenes or alkynes, thus constructing corresponding benzoheterocycle products.…”
mentioning
confidence: 99%